Components, platforms and possibilities: towards generic automation for MDA - Jackson, Ethan; Dahlweid, Markus; Seifert, Dirk; Santen, Thomas (EMSOFT, 2010)
Model-driven architecture (MDA) is a model-based approach for engineering complex software systems. MDA is particularly attractive for designing embedded systems because models can be easily evolved as hardware and software requirements evolve. However, eﬀorts to apply MDA in industrial settings expose several open problems surrounding tooling: Engineers need automated techniques that are scalable, general, and extensible. In this paper we describe the formula framework as a novel approach towards general automation for MDA. We develop a running example and benchmarks to compare our tools with other state-of-the-art approaches.